Using biosensors to measure and regulate the negative affect of drivers in simulated environments - Barnard, Megan Patricia (2017)
Recent statistics have suggested that a proportion of drivers are killed or seriously injured on UK roads due to feeling nervous, uncertain or panicked whilst driving. The literature into negative emotions has primarily focused on the relationship between anger and driving. Not including the literature on driving phobias and fears after a motor vehicle accident, the literature on the relationship between anxiety and driving is limited and inconclusive. The aim of the thesis was to investigate the effects of both state and trait anxiety on driving behaviours and autonomic reactions using studies with varying methodologies. Chapter 2 describes a questionnaire study, which found that whilst driving anxiety can have a substantial impact on anxiety related thoughts, behaviours and active avoidance, trait anxiety had slightly differential effects regarding social concerns, aggressive reactions and anxiety and avoidance of specific driving situations. Chapter 3 established, in a laboratory study, that whilst trait anxiety predicted various self-reported driving reactions, it did not affect levels of behavioural or autonomic reactions to driving video stimuli. Chapter 4 expands on these findings with a study that demonstrated reductions in high frequency heart rate variability, indicating a potential lack of emotional regulation within this context. The research was then taken into a simulated environment, where state and trait anxiety were investigated. The studies reported in Chapters 6 and 7 found limited impacts of threatening instructional sets on levels of state anxiety, but demonstrated that increases in state anxiety could lead to changes in behaviour and skin conductance levels. Finally, a simulator study reported in Chapter 8 demonstrated that whilst trait anxiety did not affect driving behaviours, it did affect levels of attentional control and processing efficiency. This leads into a discussion of the theoretical and practical implications of these findings. Particular focus is given to the benefits of interventions and exposure therapies, and it is argued that different types of intervention would be more beneficial depending on levels of state or trait anxiety.